O-020 Treatment of intracranial aneurysms with pipelinetm flex embolization device with shield technologytm : angiographic and safety outcomes at 1 year follow-up. (23rd July 2017) - MartÍnez-GaldÁmez, M; Lamin, S; Lagios, K; Liebig, T; Ciceri, E; Chapot, R; Stockx, L; Chavda, S; Kabbasch, C; Farago, G; Nordmeyer, H; Boulanger, T; et al.
Abstract : Introduction/Purpose: The Pipeline™ Embolization Device (PED) is a flow-diverter available for treatment of intracranial aneurysms (IAs). We assessed the long-term safety and angiographic outcomes of a new generation of PED, Pipeline™ Flex Embolization Device with Shield Technology™ (Pipeline™ Shield). The Pipeline™ Shield device features the same implant and delivery system as the Pipeline™ Flex Embolization Device, but has been modified to include a surface synthetic biocompatible polymer to reduce the thrombogenicity of the braid surface. Materials and Methods: The Pipeline Flex Embolization Device with Shield Technology (PFLEX) study is a prospective, single-arm, multicenter study for the treatment of unruptured IAs using Pipeline Shield. Patients with IA located in the internal carotid artery (ICA) up to the carotid terminus or vertebral artery segment up to and including the posterior inferior cerebellar artery were included. The primary study endpoint was the occurrence of major stroke in the territory supplied by the treated artery or neurological death at 1 year post-procedure. An independent Clinical Events Committee (CEC) adjudicated all adverse events. The study also assessed angiographic outcomes at 1 year post-procedure, and angiographic images in standard and working views that corresponded to the treatment angiograms were interpreted by an independent core radiology laboratory. Results: Fifty patients with 50 unruptured target IAs, 49 (98%) saccular and 1 (2%) fusiform, were treated. The mean age was 53.0±13.01 years, and 82% (41/50) of the patients were female. The mean target aneurysm diameter was 8.82±6.15 mm. Twenty-four aneurysms (48%) were small (<7 mm), 14 (28%) were medium (7–12 mm), 11 (22%) were large (13–24 mm), and 1 (2%) was giant (≥25 mm). Forty-seven (94%) aneurysms were located in the internal carotid artery, and 3 (6%) were located in the vertebral artery. Device deployment was successful in all patients. The mean number of Pipeline Shield utilized per aneurysm was 1.1±0.27. Complete wall apposition was achieved immediately post-procedure in 48 (96%) cases. No major strokes or neurological deaths were reported through 1 year post-procedure. There were 3 procedure-related, serious adverse events (headache, diplopia and retroperitoneal hematoma) and 1 device-related serious adverse event (intracranial arterythrombosis) observed through 1 year follow up. Complete aneurysm occlusion was achieved in 83.9% of target aneurysms at 1 year post-procedure. There were no reports of target aneurysm recurrence or retreatment. Conclusions: The PFLEX study is the first prospective study to evaluate the use of the Pipeline Shield device. The results from the study are comparable to previously published results with the earlier generation devices, and demonstrate that the Pipeline Shield device is safe and effective for treatment of intracranial aneurysms. Disclosures: M. Martínez-galdámez: 2; C; Proctor and consultant for Medtronic. S. Lamin: 2; C; Proctor and consultant for Medtronic. K. Lagios: None. T. Liebig: 2; C; previously consulted and proctored for Covidien, Stryker, and MicroVention, and currently serves as a proctor and consultant for Sequent Medical.. E. Ciceri: None. R. Chapot: None. L. Stockx: None. S. Chavda: None. C. Kabbasch: None. G. Farago: None. H. Nordmeyer: None. T. Boulanger: None. M. Piano: None. E. Boccardi: 2; C; receives honoraria from Medtronic and serves as a consultant for Medtronic.